2018
DOI: 10.3390/lubricants6010027
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Modeling Surface Effects in Hydrodynamic Lubrication

Abstract: Abstract:The common approach for the flow factor calculation is based on using the Reynolds equation to simulate the micro-level flow. However, for structured surfaces the fluid flow cannot be represented correctly, due to the assumptions made when deriving the Reynolds equation. In this work, a novel method using the Navier-Stokes equations for the calculation of the micro-level flow is presented and validated against results from Patir and Cheng. The three-dimensional lubrication gap was generated by a rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Furthermore, the consideration of rough contact mechanics and micro-cavitation effects also significantly affect the accuracy of the flow factor coefficients. In many successful cases, deterministic simulations of representative bearing unit cells at different length scales have been carried out to estimate the flow factors, as reported in several publications involving surface textures [155,156], honing grooves [157,158] and general roughness patterns [159][160][161][162].…”
Section: Averaging Flow Methodsmentioning
confidence: 99%
“…Furthermore, the consideration of rough contact mechanics and micro-cavitation effects also significantly affect the accuracy of the flow factor coefficients. In many successful cases, deterministic simulations of representative bearing unit cells at different length scales have been carried out to estimate the flow factors, as reported in several publications involving surface textures [155,156], honing grooves [157,158] and general roughness patterns [159][160][161][162].…”
Section: Averaging Flow Methodsmentioning
confidence: 99%
“…In [2], it has also been demonstrated that it is possible to derive the set of reduced equations for the classical lubrication approximation governing incompressible and iso-viscous flows from the full Navier-Stokes equations specialized for flows in thin gaps and applying dimensional analysis considerations. is no longer valid to describe the flow through the rough gap" [18]. The authors highlighted the advantage of Navier-Stokes equations in providing greater detail of the fluid dynamics fields with respect to Reynolds models for fluid films, thus enabling to assess the effects of structured and textured surfaces under hydrodynamic lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights the importance of the texture geometry features in the formation of the fluid films and the reduction of the transient time to reach the lubrication regime, which minimizes the damage (stress concentrations over surface roughness peaks can lead to wear debris which deteriorate the bearing performance).Pusterhofer et al[18] presented a CFD-FVM model for modelling surface effects under hydrodynamic lubrication. On the use of Reynolds models for fluid films, they stated: "for structured surfaces the fluid flow cannot be represented correctly, due to the assumptions made when deriving the Reynolds equation" [18]. Their model was based on Navier-Stokes equations, was applied to a 3D rough lubrication gap at the micro-scale, and was coupled with a Reynolds-based model working at a coarser scale.…”
mentioning
confidence: 99%
See 2 more Smart Citations